Sugar beet performance affected by uniformity of N fertigation - Nouri, Hamideh; Mohd Soom, Mohd Amin; Razavi, Seyed Jalil; Abdul Rahim, Anuar; Wayayok, Aimrun; Borujeni, Sattar Chavoshi (Science Publications, 2010)
In common with the majority of crop species, in sugar beet nutrition nitrogen is an important element due to its role in sucrose utilization and plant growth. Application of precision agriculture, in order to apply the right amount of input at the right time in the right area, is appropriate to decrease chemical use and increase plant growth. Problem statement: More often farmers apply fertilizers with low efficiency, low uniformity and high price such as spinner spreader, boom spreader or application with planting machines simultaneously. Fertigation can reduce labor cost and may improve uniformity, effectiveness and timeliness of application. Approach: The main objective of this study was to determine spatial variability of sugar beet performance affected by urea fertigation as well as established a management strategy based on spatial variability of tubers and soil total N. This study was conducted in Fesaran village, Isfahan Province of Iran and limited to sugar beet (monogerm seed). Urea applied through sprinklers. Soil samples were taken to determine soil total N as well as sugar beet tubers samples to specify yield. Results of soil and crop analysis were used to produce spatial variability maps through GS+ and ArcGIS 9.2 software. Semivariogram results were used to perform an ordinary kriging to obtain interpolated values of selected variables from the sample points through and across the study area. Results: It was found that there was a low spatial variability of soil total N and yield which indicates that the soil has a homogenous total N as well as homogenous yield through and across the field. Yield variability map of sugar beet properties demonstrated that the higher yield was seen in the southern part of the study area where laterals were closer to pump. Conclusion: The results of urea fertigation through sprinklers showed pipeline layout and pump station position impact on variability of sugar beet properties.